2015
DOI: 10.4103/0975-7406.155895
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring products in cancer therapy

Abstract: Natural products have been used for the treatment of various diseases and are becoming an important research area for drug discovery. These products, especially phytochemicals have been extensively studies and have exhibited anti-carcinogenic activities by interfering with the initiation, development and progression of cancer through the modulation of various mechanisms including cellular proliferation, differentiation, apoptosis, angiogenesis, and metastasis. This concept is gaining attention because it is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 28 publications
1
76
0
2
Order By: Relevance
“…Natural substances from plant sources, including vanillin, have gained increased interest in an alternative therapy due to their various pharmacological activities (20). Vanillin, 4-hydroxy-3-methoxybenzaldehyde ( Fig.…”
Section: Suppression Of Cancer Stem-like Phenotypes In Nci-h460 Lung mentioning
confidence: 99%
“…Natural substances from plant sources, including vanillin, have gained increased interest in an alternative therapy due to their various pharmacological activities (20). Vanillin, 4-hydroxy-3-methoxybenzaldehyde ( Fig.…”
Section: Suppression Of Cancer Stem-like Phenotypes In Nci-h460 Lung mentioning
confidence: 99%
“…2 Many studies with plant extracts revealed that some of these plants had anti-tumor activity, thus being a source of compounds for successful development of anticancer drugs. 3,4 One example is paclitaxel (Taxol), derived from Taxus brevifolia (from the family Taxaceae) and currently clinically used in the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas single synthetic molecules were favored for targeted therapies in the past, they have been associated with shortcomings including toxicity, high cost, and drug resistance phenotypes [14,15]. Natural home medicine ingredients have been shown to provide a safer and holistic remedies for treatment of stress and cancer and are often predicted to offer additional benefits such as higher and broad spectrum efficacy [16,17].…”
Section: Introductionmentioning
confidence: 99%